Implementation of Extracurricular Activities and Additional Season Olympiad Class to Enhance Learning Achievement - Safira, Annisa Sofi; Juhadi, Juhadi; Arsal, Thriwarty (JESS (Journal of Educational Social Studies), 2025)
Extracurricular is a program that can be implemented to serve as a platform for students to enhance their abilities outside of the regular class. The research strives to indentifying the impact of the implementation of extracurricular activities and extra class for Olympiad preparation on students' academic performance at MAN 2 Semarang City. The research was conducted at MAN 2 Semarang City, using a quantitative research method, with data collection through questionnaires and documentation. The activities available at MAN 2 Kota Semarang include: PMR, Pencak Silat, Dance Arts, Rebana, Music/Band, Futsal, Cinematography, Volleyball, English Club, MTQ, Basketball, KIR, Scouts, and Paskibra. The additional lesson is carried out daily for students in the Olympiad class with the subjects including geography, economics, English, and earth sciences from the social field, and physics, mathematics, chemistry, and biology from the science field. Based on the research findings, the implementation of the extracurricular activities and the additional lesson has an impact on students' learning achievements.